Karakteristik Penggunaan Adjektiva dalam Iklan Produk Kecantikan - Oktaviani, Intan; Agustina (Universitas Negeri Padang, 2024)
Adjectives are words used to describe the qualities or states of nouns, including living things, objects, and concepts. In advertisements, adjectives are frequently employed in various forms and styles to attract consumers. This study aims to analyze and describe: (1) the forms of adjectives used in beauty product advertisements, (2) the degrees or levels of adjectives used in beauty product advertisements, and (3) the semantic functions of adjectives used in beauty product advertisements. This qualitative research employed a descriptive method. The data consisted of words and phrases containing adjectives in various forms, degrees, and semantic functions, extracted from beauty product advertisements on Female Daily magazine's online platform. Data was collected through observation and note-taking. The data collection process involved opening Google, taking screenshots of product descriptions on Female Daily containing adjectives, and identifying the adjectives relevant to the study. Data analysis was conducted in four stages: classifying data according to research objectives, analyzing data, discussing data, and drawing conclusions and reporting the research findings. Based on the research findings, the following conclusions were drawn. Firstly, based on their forms, two types of adjectives were found: (1) basic forms, and (2) derived forms, which include affixed, reduplicated, and compound adjectives. Secondly, based on their degrees, four types of adjectives were found: (1) positive degree, (2) comparative degree, (3) superlative degree, and (4) emphatic degree. Thirdly, based on their functions, eight semantic functions of adjectives were found: (1) stative, (2) durative, (3) affective, (4) benefactive, (5) causative, (6) possessive, (7) habitual, and (8) comparative.